Preparation and application of flower-like nickel-cobalt-zinc hydroxide carbonate nanohollow sphere material

CN116705519BActive Publication Date: 2026-10-30HARBIN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310499876.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-05
Publication Date
2026-10-30
Estimated Expiration
2043-05-05

AI Technical Summary

Technical Problem

[0007]本发明的目的是解决镍钴碱式碳酸盐体积变化大,循环稳定性差,导电性低的问题,而提供一种花状镍钴锌碱式碳酸盐纳米空心球超级电容器电极材料的制备方法

Benefits of technology

[0010](1)本发明制备了一种花状镍钴锌碱式碳酸盐纳米空心球超级电容器电极材料能够有效镍钴碱式碳酸盐体积变化大,循环稳定性差,导电性低的问题。其中元素取代是进一步提高电导率的有效方法。加入适量的Zn元素可以加速电子和离子的转移,提高镍钴锌碱式碳酸的电化学稳定性和活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116705519B_ABST
    Figure CN116705519B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of flower-shaped nickel-cobalt-zinc basic carbonate nanohollow sphere material as supercapacitor electrode material. The application aims to solve the problems of large volume change, poor cycle stability and low conductivity of nickel-cobalt basic carbonate. The application mainly comprises: 1. Solvothermal synthesis of nickel-cobalt-zinc glycerate; 2. Solvothermal synthesis of nickel-cobalt-zinc basic carbonate. The two-step solvothermal method has the characteristics of simple synthesis process, low cost, high yield and no subsequent treatment, etc. The preparation of flower-shaped nickel-cobalt-zinc basic carbonate supercapacitor electrode material provides a large contact area and rich active sites on the electrolyte electrode, and shortens the ion transmission path. The hollow structure also improves the cycle stability by releasing stress and reducing the volume change during charging / discharging. The prepared flower-shaped nickel-cobalt-zinc basic carbonate nanohollow sphere supercapacitor electrode material has a specific capacitance of 792.6 C g ‑1 -1 at 1 Ag ‑1 -1, and has an excellent cycle performance of 87.9% in 10000 cycles at 10 Ag ‑1 -1. In a two-electrode system, when the power density is 400 W kg ‑1 -1, the energy density can reach 33.7 Wh kg ‑1 -1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of material preparation and energy storage, and more specifically, to a method for preparing a flower-shaped nickel-cobalt-zinc basic carbonate nano-hollow sphere supercapacitor electrode material. Background Technology

[0002] With the rapid depletion of fossil fuels and increasing environmental pollution, the development of renewable and clean energy is imperative. Common renewable energy sources such as wind, solar, and tidal power require high-energy-density energy storage devices to store electricity. Supercapacitors, with their excellent electrochemical performance—high specific capacitance, high power density, long cycle life, low cost, and safe and stable operation—have attracted widespread attention as high-performance energy storage devices.

[0003] As a typical pseudocapacitive electrode material, transition metal basic carbonates exhibit excellent capacitance performance. The carbonate ions improve the wettability of the electrode surface and address the issue of unsatisfactory capacitance of transition metal hydroxides in aqueous electrolytes. This facilitates electrolyte penetration into the electrode material and promotes ion transfer during redox reactions.

[0004] Currently, several high-specific-capacity nickel-cobalt basic carbonates have been developed in various forms, such as nanoneedles, nanoribbons, urchin-like structures, and flower-like forms. However, issues such as large volume variations, poor cycle stability, and low conductivity have affected the energy storage capacity of nickel-cobalt basic carbonates and their large-scale production and application.

[0005] Compared to the aforementioned morphologies, the hollow structure provides channels for electrolyte diffusion, enhances the contact area between the electrolyte and the electrode, and releases stress during charge and discharge to reduce volume changes, thus ensuring the cycling stability of the electrode. The self-templating method can obtain hollow structures, eliminate heterogeneous growth, simplify the process, and better control the uniformity of the material. Element substitution is an effective method to further improve conductivity. Adding an appropriate amount of Zn can accelerate electron and ion transfer, improving the electrochemical stability and activity of nickel-cobalt basic carbonates.

[0006] In summary, this invention has prepared a flower-shaped nickel-cobalt-zinc basic carbonate hollow nanosphere material. Due to its hollow structure and the synergistic effect between the multiple transition metals, it has excellent electrochemical performance and has good application prospects as an electrode material for supercapacitors. Summary of the Invention

[0007] The purpose of this invention is to solve the problems of large volume change, poor cycle stability and low conductivity of nickel-cobalt basic carbonate, and to provide a method for preparing flower-shaped nickel-cobalt-zinc basic carbonate nano-hollow sphere supercapacitor electrode material.

[0008] The preparation method of the flower-shaped nickel-cobalt-zinc basic carbonate nano-hollow sphere supercapacitor electrode material of the present invention is carried out according to the following steps: I. Preparation of Nickel Cobalt Zinc Glycerate by Solvent Thermothermal Synthesis 1) Dissolve 1–3 mmol nickel nitrate hexahydrate, 1–3 mmol cobalt nitrate hexahydrate, and 0–1 mmol zinc nitrate hydrate in a mixed solution of 30–50 mL isopropanol and 6–10 mL glycerol. Add 0.1–0.4 g polyvinylpyrrolidone (K30) to the above mixed solution and stir for 30 min. 2) Pour the mixed solution from step 1) into an autoclave and maintain it at 160–200°C for 4–8 hours. Finally, centrifuge and wash repeatedly with ethanol three times, then dry at 60°C for 12 hours to obtain nickel cobalt zinc glycerate. II. Preparation of Nickel-Cobalt-Zinc Basic Carbonates by Solvent Thermothermal Synthesis Weigh 40-80 mg of nickel cobalt zinc glycerate from step 1(2) and ultrasonically disperse it into 40-80 mL of ethanol / water mixed solution (volume ratio 1:1). After ultrasonic treatment for 15 min, add 5-10 mmol of urea to the above dispersion solution and stir for 30 min. Then, place the above mixture in an autoclave and maintain it at 120-180℃ for 6-10 h. Collect the blue-green precipitate by centrifugation, wash it repeatedly with ethanol three times to remove impurities, and dry it at 60℃ for 12 h to obtain flower-shaped nickel cobalt zinc basic carbonate hollow nanosphere material.

[0009] Compared with existing technologies, the present invention has the following advantages:

[0010] (1) This invention prepares a flower-shaped nickel-cobalt-zinc basic carbonate nano-hollow sphere supercapacitor electrode material, which effectively addresses the problems of large volume change, poor cycle stability, and low conductivity of nickel-cobalt basic carbonate. Element substitution is an effective method to further improve conductivity. Adding an appropriate amount of Zn can accelerate the transfer of electrons and ions, and improve the electrochemical stability and activity of nickel-cobalt-zinc basic carbonate.

[0011] (2) The flower-shaped nickel-cobalt-zinc basic carbonate nano-hollow sphere supercapacitor electrode material prepared by the present invention has uniform morphology and size, effectively increasing the specific surface area and the number of active sites of the material, and improving the conductivity of the electrode material. Its hollow structure provides a channel for the diffusion of electrolyte, enhances the contact area between electrolyte and electrode, and releases stress during charging and discharging to reduce volume change, thus ensuring the cycle stability of the electrode. Attached Figure Description

[0012] Figure 1 This is a photograph showing the appearance and morphology of a flower-shaped nickel-cobalt-zinc basic carbonate hollow nanosphere material. Figure 2 It describes the crystal and chemical structure of a flower-shaped nickel-cobalt-zinc basic carbonate hollow nanosphere material. Figure 3 The electrochemical properties of a flower-shaped nickel-cobalt-zinc basic carbonate hollow nanosphere material prepared; Figure 4 The accompanying figure for the abstract is a hollow nanosphere with a two-dimensional nanosheet structure and a size of approximately 800 nm. Detailed Implementation

[0013] Specific Implementation Method 1: A method for preparing a flower-shaped nickel-cobalt-zinc basic carbonate nano-hollow sphere supercapacitor electrode material, specifically carried out according to the following steps: I. Preparation of Nickel Cobalt Zinc Glycerate by Solvent Thermothermal Synthesis 1) Dissolve 1–3 mmol nickel nitrate hexahydrate, 1–3 mmol cobalt nitrate hexahydrate, and 0–1 mmol zinc nitrate hydrate in a mixed solution of 30–50 mL isopropanol and 6–10 mL glycerol. Add 0.1–0.4 g polyvinylpyrrolidone (K30) to the above mixed solution and stir for 30 min. 2) Pour the mixed solution from step 1) into an autoclave and maintain it at 160–200°C for 4–8 hours. Finally, centrifuge and wash repeatedly with ethanol three times, then dry at 60°C for 12 hours to obtain nickel cobalt zinc glycerate. II. Preparation of Nickel-Cobalt-Zinc Basic Carbonates by Solvent Thermothermal Synthesis Weigh 40-80 mg of nickel cobalt zinc glycerate from step 1(2) and ultrasonically disperse it into 40-80 mL of ethanol / water mixed solution (volume ratio 1:1). After ultrasonic treatment for 15 min, add 5-10 mmol of urea to the above dispersion solution and stir for 30 min. Then, place the above mixture in an autoclave and maintain it at 120-180℃ for 6-10 h. Collect the blue-green precipitate by centrifugation, wash it repeatedly with ethanol three times to remove impurities, and dry it at 60℃ for 12 h to obtain flower-shaped nickel cobalt zinc basic carbonate hollow nanosphere material.

[0014] Specific Implementation Method Two: A method for preparing a flower-shaped nickel-cobalt-zinc basic carbonate nano-hollow sphere supercapacitor electrode material, specifically carried out according to the following steps: The difference between this embodiment and Specific Embodiment 1 is that the solvent used in the preparation of nickel cobalt zinc glycerate in step one is isopropanol and glycerol, and the preparation of nickel cobalt zinc glycerate uses 0.1-0.3g of polyvinylpyrrolidone (K30). Everything else is the same as in Specific Embodiment 1.

[0015] Specific Implementation Method 3: A method for preparing a flower-shaped nickel-cobalt-zinc basic carbonate nano-hollow sphere supercapacitor electrode material, specifically carried out according to the following steps: The difference between this embodiment and one of the specific embodiments one or two is that the solvothermal reaction temperature in step one (2) is 170℃~190℃ and the reaction time is 5~7h. It is the same as one of the specific embodiments one or two.

[0016] Specific Implementation Method Four: A method for preparing a flower-shaped nickel-cobalt-zinc basic carbonate nano-hollow sphere supercapacitor electrode material, specifically carried out according to the following steps: The difference between this embodiment and one of the specific embodiments one to three is that the solvent used in the preparation of nickel cobalt zinc basic carbonate in step two is ethanol / water, the solvothermal reaction temperature is 130℃~150℃, the reaction time is 7~9h, and 5~10mmol of urea is used in the preparation of nickel cobalt zinc basic carbonate to obtain flower-shaped nickel cobalt zinc basic carbonate hollow nanosphere materials.

[0017] The following experiments were conducted to verify the effectiveness of the present invention: The preparation method of the flower-shaped nickel-cobalt-zinc basic carbonate nano-hollow sphere supercapacitor electrode material in this experiment is carried out according to the following steps: I. Preparation of Nickel Cobalt Zinc Glycerate by Solvent Thermothermal Synthesis

[0018] 1) Dissolve 1 mmol nickel nitrate hexahydrate, 1 mmol cobalt nitrate hexahydrate and 0.25 mmol zinc nitrate hydrate in a mixed solution of 40 mL isopropanol and 8 mL glycerol. Add 0.1 g polyvinylpyrrolidone (K30) to the above mixed solution and stir for 30 min.

[0019] 2) Pour the mixture from step 1) into an autoclave and maintain it at 180°C for 6 hours. Finally, centrifuge and wash repeatedly with ethanol three times, then dry at 60°C for 12 hours to obtain nickel cobalt zinc glycerate. II. Preparation of Nickel-Cobalt-Zinc Basic Carbonates by Solvent Thermothermal Synthesis Weigh 60 mg of nickel cobalt zinc glycerate from step 1) and ultrasonically disperse it into 60 mL of ethanol / water mixed solution (volume ratio 1:1). After ultrasonic treatment for 15 min, add 6 mmol of urea to the above dispersion solution and stir for 30 min. Then, place the above mixture in an autoclave and keep it at 140 °C for 8 h. Collect the blue-green precipitate by centrifugation, wash it repeatedly with ethanol three times to remove impurities, and dry it at 60 °C for 12 h to obtain flower-shaped nickel cobalt zinc basic carbonate hollow nanosphere composite material.

[0020] This invention uses a three-electrode testing system to study the electrochemical performance of materials. A foil is used as the counter electrode, a saturated Ag / AgCl electrode as the reference electrode, a platinum wire as the counter electrode, and the aforementioned flower-shaped nickel-cobalt-zinc basic carbonate hollow nanosphere material as the working electrode. Electrochemical detection is performed using a 6M potassium hydroxide solution as the electrolyte.

[0021] Figure 1 These are photographs showing the morphology of a flower-shaped nickel-cobalt-zinc basic carbonate hollow nanosphere. Figure 1 Images a and b show scanning electron microscope (SEM) images of nickel-cobalt-zinc basic carbonate nanospheres with diameters of 400 nm and 800 nm, respectively, and SEM images of flower-shaped hollow nickel-cobalt-zinc basic carbonate nanospheres. The elemental spectrum of the flower-shaped hollow nickel-cobalt-zinc basic carbonate nanospheres shows that Ni, Co, Zn, C, and O are uniformly distributed. Figure 1 c), Transmission electron microscopy image of flower-shaped nickel-cobalt-zinc basic carbonate hollow nanospheres ( Figure 1 d). The flower-like nickel-cobalt-zinc basic carbonate hollow nanosphere is a hollow nanosphere with a size of approximately 800 nm and a cavity of approximately 400 nm. Figure 1 e). Figure 1 f shows two lattice fringe spaces of 0.228 nm and 0.256 nm for the flower-shaped nickel-cobalt-zinc basic carbonate nanospheres, corresponding to the (231) and (040) crystal planes of cobalt-based bicarbonate (PDF 48-0083), respectively. SAED plots show two diffraction rings representing the (221) plane of basic nickel carbonate and the (412) plane of basic cobalt carbonate crystals.

[0022] Figure 2 The crystal and chemical structures of a flower-like nickel-cobalt-zinc basic carbonate hollow nanosphere were prepared. Figure 2 a represents the XRD patterns of glycerol nickel cobalt zinc, nickel cobalt hydroxide, and flower-shaped nickel cobalt zinc basic carbonate hollow nanospheres, showing the positions of the diffraction peaks and their corresponding planes. Glycerol nickel cobalt zinc has a prominent peak at 10°, indicating the presence of a metal alkoxide. For nickel cobalt hydroxide, the three diffraction peaks at 2θ = 33.5° and 59.8° correspond to (221) and (412) of basic cobalt carbonate, and 2θ = 12.6° corresponds to (040) of basic nickel carbonate. For nickel cobalt zinc hydroxide, the diffraction peaks are similar to those of nickel cobalt hydroxide. The difference lies in the fact that, due to Zn 2+ The ionic radius of (0.74 Å) is greater than that of Co. 2+ The (0.745Å) peak is short, and the diffraction peak shifts to the right. Therefore, Zn 2+ The doping of Zn leads to a reduction in lattice space, proving that Zn 2+ Successfully doped into nickel cobalt hydroxide, Figure 2b describes the XPS spectra of Ni, Co, Zn, C, and O. The atomic ratio of Zn, Ni, and Co is 2.58:8.65:9.39, which is almost consistent with the EDS results above. Figure 2 c shows the deconvolution peaks of the Ni2p spectrum at 873.3 eV and 855.7 eV for Ni2p. 1 / 2 and Ni2p 3 / 2 The intervals of 17.6 eV and two satellite peaks indicate the presence of Ni in the flower-like nickel-cobalt-zinc basic carbonate hollow nanospheres. 2+ , Figure 2 d indicates that the Co2p spectrum can be decomposed into Co2p 1 / 2 (796.7 eV) and Co2p 3 / 2 The two main peaks (780.9 eV) indicate the presence of Co in Co-CH. 2+ Zn2p spectrum ( Figure 2 e) represent Zn2p 1 / 2 (1044.7 eV) and Zn 2+ 2p 3 / 2 The two main peaks (1021.5 eV) clearly indicate that Zn in nickel-cobalt hydroxide... 2+ The presence of this indicates the formation of flower-like nickel-cobalt-zinc basic carbonate hollow nanospheres. The C1s peak can be divided into three peaks ( Figure 2 f): OC = O (288.5 eV), CO (286.1 eV) and non-deoxygenated carbon (284.5 eV, indicating the presence of CO32-). 2- . Figure 2 g indicates that the O1s spectrum can be attributed to hydroxide groups (530.2 eV) and carbonate groups (531.2 eV).

[0023] Figure 3 This study describes the electrochemical performance of a flower-shaped nickel-cobalt-zinc basic carbonate hollow nanosphere; the three-electrode electrochemical performance of the flower-shaped nickel-cobalt-zinc basic carbonate hollow nanosphere is shown. All CV curves for these electrodes are obtained at 60 mVs in the range of 0–0.6 V. -1 The scan rate showed obvious redox peaks, and when Zn 2+ As the amount added increases, the integral area first increases, then decreases. Figure 3 a). Flower-shaped nickel-cobalt-zinc basic carbonate hollow nanospheres exhibit the largest integrated area and the highest peak current, which is consistent with Zn 2+ The appropriate addition of Zn is relevant. 2+ Doping with Zn can effectively improve the conductivity of electrode materials, but Zn only has one valence state and cannot contribute much capacity. Therefore, excessive addition of Zn is not recommended. 2+ This will reduce electrochemical performance. Furthermore, as the scan rate increases from 10 mV s⁻¹... -1Increased to 100mV s -1 The oxidation and reduction peaks of the flower-shaped nickel-cobalt-zinc basic carbonate nano-hollow sphere electrode gradually shift to higher or lower potentials. Figure 3 (b) Notably, the CV curves maintained similar and symmetrical profiles, showing no significant change with increasing scan rate, indicating good reversibility and excellent rate characteristics. The presence of reversible redox reactions during the electrochemical process confirms the electrode behavior. (Vs from 10 to 100 mV) -1 The Faraday peak currents of the flower-shaped nickel-cobalt-zinc basic carbonate hollow nanosphere electrodes were 30.71, 45.60, 64.87, 78.28, 88.78, 97.76 and 19.29, 30.10, 45.33, 57.55, 67.79, 76.52, respectively. The absolute values ​​of the anode peak and cathode peak values ​​were 0.5014 and 0.5976, respectively, indicating that battery-like behavior was dominant. Figure 3 c), the GCD curves of the flower-shaped nickel-cobalt-zinc basic carbonate hollow nanospheres were plotted. Figure 3 d). Notably, the clear charge / discharge plateau and nearly symmetrical curves further illustrate the battery-like behavior of the electrodes. When Zn 2+ With increasing addition, the charge / discharge time initially increased and then decreased, with the flower-shaped nickel-cobalt-zinc basic carbonate hollow nanospheres exhibiting the longest discharge time. Simultaneously, symmetrical GCD curves indicate that the Faraday redox reaction of the flower-shaped nickel-cobalt-zinc basic carbonate hollow nanospheres exhibits excellent reversibility and coulombic efficiency. Figure 3 e shows the GCD curves of flower-shaped nickel-cobalt-zinc basic carbonate hollow nanospheres, providing values ​​from 1 to 10 A g. -1 The values ​​of 792.6, 760.3, 678.4, 611.7, 557.7, and 513.1 g are mentioned. -1 High specific capacity. Furthermore, such as... Figure 3 As shown in f, the flower-shaped nickel-cobalt-zinc basic carbonate hollow nanospheres exhibit good rate performance in the range of 1 to 10 A g. -1 It exhibits a specific capacity retention of approximately 72.3% at current densities. Figure 3 g shows the Nyquist plots of these electrodes. The charge transfer resistance (Rs) is represented by the intercept of the semicircle contacting the x-axis, and the internal resistance (Rct) is the radius of the semicircle in the high-frequency region. Long-term cycling stability is also an important aspect of evaluating the electrochemical performance of electrode materials. Figure 3 As shown in h, at 10A g -1In 10,000 cycles, the flower-shaped nickel-cobalt-zinc basic carbonate hollow nanospheres exhibited excellent cycling performance of 87.9% and excellent coulombic efficiency of 100%, indicating that the hollow structure can provide effective electrolyte permeation and stress release to improve the cycling stability of the electrode material during long-term charge / discharge processes.

Claims

1. A method for preparing flower-shaped nickel-cobalt-zinc basic carbonate hollow nanospheres, characterized in that... A method for preparing a supercapacitor electrode material of flower-shaped nickel-cobalt-zinc basic carbonate nano-hollow spheres is carried out according to the following steps: I. Preparation of Nickel Cobalt Zinc Glycerate by Solvent Thermothermal Synthesis 1) Dissolve 1–3 mmol nickel nitrate hexahydrate, 1–3 mmol cobalt nitrate hexahydrate, and 0–1 mmol zinc nitrate hydrate in a mixed solution of 30–50 mL isopropanol and 6–10 mL glycerol. Add 0.1–0.4 g polyvinylpyrrolidone K30 to the above mixed solution and stir for 30 min. 2) Pour the mixture from step 1) into an autoclave and maintain it at 160–200°C for 4–8 hours. Finally, centrifuge and wash repeatedly with ethanol three times, then dry at 60°C for 12 hours to obtain nickel cobalt zinc glycerate. II. Preparation of Nickel-Cobalt-Zinc Basic Carbonates by Solvent Thermothermal Synthesis Weigh 40-80 mg of nickel cobalt zinc glycerate from step 1(2), disperse it by ultrasonication into 40-80 mL of ethanol / water mixed solution with a volume ratio of 1:1, and ultrasonically treat for 15 min. Then, add 5-10 mmol of urea to the above dispersion solution and stir for 30 min. Then, place the above mixture in an autoclave and keep it at 120-180℃ for 6-10 h. Collect the blue-green precipitate by centrifugation, wash it repeatedly with ethanol three times to remove impurities, and dry it at 60℃ for 12 h to obtain flower-shaped nickel cobalt zinc basic carbonate hollow nanosphere material.

2. According to the preparation method of claim 1, the preparation of nickel cobalt zinc glycerate uses 0.1-0.3g of polyvinylpyrrolidone K30.

3. The preparation method according to claim 1, characterized in that... In step 1, 2), the solvothermal reaction temperature is 170℃~190℃, and the reaction time is 5~7h.

4. The preparation method according to claim 1, characterized in that... The solvothermal reaction temperature in step two is 130℃~150℃, and the reaction time is 7~9h.

Citation Information

Patent Citations

  • Neutral zwitterionic displacer molecules for hydrophobic displacement chromatography

    CN103958016A

  • Pine needle-shaped nickel-cobalt-copper basic carbonate nano composite material as well as preparation method and application thereof

    CN110890227A